Strategic Outsourcing: A Holistic Analysis of An Ooutsourcing Operation At A UK SME - Phillips, Dane (2006)
An analysis of the decision to outsource peripheral functions to an international partner, by a UK SME in the professional services industry. Paper focuses on a broad analysis of the contractual, negotiation and resistance issues that a firm might face when engaging in outsourcing practices, and attempts an analysis of the tangible gains that can result from a well planned, well managed outsourcing arrangement. Paper considers a review of the benefits and risks associated with outsourcing, the resource based view versus the transaction cost economic theory, traditional and strategic outsourcing theory, as well as a brief commentary on the future of outsourcing, from a global perspective.